Bandwidth Prediction Based Resource Allocation Scheme for Low-Latency and Energy-Efficient PONs With Heterogeneous ONU Propagation Delays - Pengcheng Li; Yunxin Lv; Meihua Bi (IEEE Photonics Journal, 2024)
To achieve low-latency and energy-efficient in a 10 Gbps Ethernet Passive Optical Network (10G-EPON) having heterogeneous Optical Network Unit (ONU) propagation delays, this article proposes a resource allocation scheme based on bandwidth requirements prediction and ONU polling sequence scheduling. By a) predicting the upstream (US) and downstream (DS) bandwidth requirements of each ONU using Long Short-Term Memory (LSTM) networks and b) arranging the ONU polling sequence and the US and DS transmission start times of each ONU based on the predicted bandwidth requirements and the ONU propagation delays, the proposed scheme minimizes bandwidth waste of the network as well as the overall operating time of each ONU. Therefore, low-latency performance is achieved, and the energy consumption of ONUs is reduced as ONU sleeping time is extended. Simulation results indicate that the proposed scheme reduces network latency and improves energy efficiency effectively. Compared to the conventional Interleaved Polling with Adaptive Cycle Time scheme that adopts the shortest propagation delay first rule and ONU doze mode, the proposed scheme can reduce the average one-way packet delay by at least 28.9%, and can reduce the per bit energy consumption by 73.7% when concerning data transmitted under the 1 ms latency constraint.